(untitled) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Circulating blood; total count; differential count; B. melanostictus; H. flaviviridis Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 39-42